Analysis of Impulsive Buying Behavior in Fashion Industry - Saamarth Gandhi (International Journal of Engineering and Management Research, 2020)
In this era of rising customer expectations and intense competitions, marketers and retailers constantly look towards means to maximize their customers’ share of wallet, in terms of additional sales. Marketers, today, thus focus on the customers’ preferences, their needs and wishes with an aim to maximize it. Impulse shopping can be termed as a spontaneous, immediate purchase without pre-shopping intentions either to buy a specific product category or to fulfil a specific buying task. Impulse buying is a major research concern among marketers due to its pervasive aspects of consumer behavior as well as its potential in the marketing world. Based on the literature review, and after considering the questions we want to answer, the research problem of the research paper is “Analysis of Impulse Buying Behavior in the Fashion Industry”. This problem would specifically be emphasizing on the factors which affect such behavior, post purchase feelings and behavior and how online shopping has increased the propensity of such behavior. Based on the research problem of our paper, given below are the 4 major objectives which the paper will studying and analysing: Determining and comparing the various internal and external factors which affect Impulse Buying Behavior in the Fashion Industry. Analysing The Impulse Buying Behavior Towards Different Fashion Product Categories Analysing The Post Purchase Feeling and Behavior as A Result of Impulse Buying Behavior Determining the impact of growing E-commerce industry on impulse shopping behavior in the fashion industry, and the factors leading to it. Methodology used in research paper is SINGLE CROSS SECTIONAL DESCRIPTIVE DESIGN. Given the objective and design of our research, we will be using basic descriptive statistics i.e. Mean, Median and Mode to compare and analyse our data and conclude our findings. Finally, the findings for the research essentially indicated that amongst the external factors, Overall store environment and lower prices played a pivotal role. Moreover, males tend to shop more impulsively as compared to females. Customers tend to show a positive impulse behavior towards Footwear and Clothing items. Happiness is seen to be the most common post purchase behavior. Lastly, the research also presented an evidence showing that the emergence of e-commerce positively impacted impulse buying behavior, with Heavy Discounting being its most prominent driver.